Effects of manual therapy and inclined board standing on low back pain: a pilot study - Muhammad Hafeez; Muhammad Zia Ul Haq; Shabana Rahim (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Low back pain (LBP), especially mechanical in nature, affects approximately 577 million people globally. Its incidence is expected to rise due to an ageing population. This study aims to assess the impact of Manual Therapy and Inclined Board Standing on LBP management. METHODOLOGY: This pilot study involved 10 patients (6 females, 4 males) aged 18-65 with LBP. Participants were randomly assigned to two groups: Group A received manual therapy with passive hip lateral rotator stretching and inclined board standing. In contrast, Group B received routine medication and inclined board standing. Data were collected at baseline, one week, and two weeks post-intervention. Pain, disability, and quality of life were measured using the NPRS, ODI, and SF-12. Ethical approval and informed consent were obtained. RESULTS: The results revealed significant improvements post-treatment. Pain showed a mean difference of 1.70 (SD = 0.67), t(9) = 7.97, p < .001. Disability (ODI) had a mean difference of 0.90 (SD = 0.74), t(9) = 3.86, p = .004. Quality of life improved with a mean difference of 0.60 (SD = 0.52), t(9) = 3.67, p = .005. Repeated measures ANOVA confirmed these findings: pain (F(1, 9) = 63.439, p < .001), disability (F(1, 9) = 14.878, p = .004), and QOL (F(1, 9) = 13.500, p = .005). CONCLUSION: Manual therapy, passive stretching, and inclined board standing are more effective than inclined board standing alone in managing low back pain and improving lumbar spine function.